Development of comic-based electronic modules using canva design in elements periodic system material in class X SMA/MA - Norma Yunita; Roza Linda; Asmadi M Noer (Jurnal Pendidikan Kimia (JPKIM), 2023)
This study intends to create comic-based electronic modules using Canva design with accurate elemental periodic system content and find out how learners react to comic-based electronic modules.  The research is of the type known as research and development (R&D), which is based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). However, for small-scale trials, this step is only completed up to the implementation stage.  The module developed is a comic-based electronic module using one of the applications, namely Canva Design to overcome the problems of students' difficulties in understanding the elemental periodic system material and increase students' learning motivation. Three validators, including two material experts and one media expert, evaluated the electronic module based on comic books. The validation of material specialists yielded a percentage of 98.44% in the valid category based on factors such as content viability, comic features, language, presentation, and graphics. A percentage of 98.86% was attained in the valid category for the media expert validation results based on a visual communication display and software usage. In the teacher response trials, students obtained an overall percentage of 87.66% while teachers received an 87% in the very good category. The comic-based electronic module created using a Canva design is legitimate and appropriate for use in content related to the elements of the periodic system, according to data analysis.Keywords: Comic-Based Electronic Module; Canva Design; Periodic System of Elements